SABUN RUMPUT LAUT NEGERI LASKAR PELANGI - Apriyanto, Haris; Hafizh, Awwab; Zahara, Siti; Pebriandi, Eka (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
The most commonly used chemicals for making the soaps are less safe for human skin. Soap contains ingredients that are safe and nutritious for the skin need to be developed. Seaweed is one of the potential mariculture commodities in Bangka Belitung Islands Province.. The purpose of this activity is the utilization of seaweed for making the soap using direct experimental methods in order to generate the profit. Business analysis was performed to determine the advantages and feasibility. This study revealed that seaweed can be used as raw material for making safe and profitable soap with a soft texture.Â Keywords: soap, seaweed, safe, nutritious, soft